The Stopping the Spread of Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome through Relationship Engagement Study: An Opportunity for Human Immunodeficiency Virus Prevention in African American Adolescents with HIV-Positive Mothers - Ndidiamaka Amutah-Onukagha; Vanessa Nicholson; Yoann S. Antoine; Telesha Zabie; Lorraine Lacroix-Williamson; Ruth Vigue; Elizabeth Bolarinwa (HIV/AIDS Research and Treatment-Open Journal, 2022)
In 2018 Blacks/African Americans made up 13% of the female population but accounted for 58% of diagnoses of human immunodeficiency virus (HIV) infection among females. Studies show that women have always been underrepresented in HIV/acquired immune deficiency syndrome (AIDS) studies, however, the coronavirus disease-2019 (COVID-19) pandemic has further exacerbated the existing barriers in HIV research.